Elevation of fatty acid desaturase 2 in esophageal adenocarcinoma increases polyunsaturated lipids and may exacerbate bile acid‐induced DNA damage. Issue 5 (12th May 2022) - Molendijk, Jeffrey; Kolka, Cathryn M.; Cairns, Henry; Brosda, Sandra; Mohamed, Ahmed; Shah, Alok K.; Brown, Ian; Hodson, Mark P.; Hennessy, Thomas; Liu, Guanghao; Stoll, Thomas; Richards, Renee S.; et al.
Abstract: Background: The risk of esophageal adenocarcinoma (EAC) is associated with gastro‐esophageal reflux disease (GERD) and obesity. Lipid metabolism‐targeted therapies decrease the risk of progressing from Barrett's esophagus (BE) to EAC, but the precise lipid metabolic changes and their roles in genotoxicity during EAC development are yet to be established. Methods: Esophageal biopsies from the normal epithelium (NE), BE, and EAC, were analyzed using concurrent lipidomics and proteomics ( n = 30) followed by orthogonal validation on independent samples using RNAseq transcriptomics ( n = 22) and immunohistochemistry (IHC, n = 80). The EAC cell line FLO‐1 was treated with FADS2 selective inhibitor SC26196, and/or bile acid cocktail, followed by immunofluorescence staining for γH2AX. Results: Metabolism‐focused Reactome analysis of the proteomics data revealed enrichment of fatty acid metabolism, ketone body metabolism, and biosynthesis of specialized pro‐resolving mediators in EAC pathogenesis. Lipidomics revealed progressive alterations (NE‐BE‐EAC) in glycerophospholipid synthesis with decreasing triglycerides and increasing phosphatidylcholine and phosphatidylethanolamine, and sphingolipid synthesis with decreasing dihydroceramide and increasing ceramides. Furthermore, a progressive increase in lipids with C20 fatty acids and polyunsaturated lipids with ≥4 double bonds were also observed. Integration with transcriptome data identified candidate enzymes for IHC validation: Δ4‐Desaturase, Sphingolipid 1 (DEGS1) which desaturates dihydroceramide to ceramide, and Δ5 and Δ6‐Desaturases (fatty acid desaturases, FADS1 and FADS2), responsible for polyunsaturation. All three enzymes showed significant increases from BE through dysplasia to EAC, but transcript levels of DEGS1 were decreased suggesting post‐translational regulation. Finally, the FADS2 selective inhibitor SC26196 significantly reduced polyunsaturated lipids with three and four double bonds and reduced bile acid‐induced DNA double‐strand breaks in FLO‐1 cells in vitro. Conclusions: Integrated multiomics revealed sphingolipid and phospholipid metabolism rewiring during EAC development. FADS2 inhibition and reduction of the high polyunsaturated lipids effectively protected EAC cells from bile acid‐induced DNA damage in vitro, potentially through reduced lipid peroxidation. Abstract : Multiomic techniques were applied to the normal esophagus, Barrett's esophagus, and esophageal adenocarcinoma (EAC) tissues to investigate lipid metabolism. Polyunsaturated lipids, desaturase pathways, and antioxidant processes were upregulated as the disease progresses. Blocking fatty acid desaturase 2 protects an EAC line from bile acid‐induced DNA damage.